Design and Implementation of Double Loop Control Strategy in TPFW Voltage and Current Regulated Inverter for Photovoltaic Application - Leonardus Heru Pratomo; Agutinus Fidelis Wibisono; Slamet Riyadi (Universitas Muhammadiyah Yogyakarta, 2022)
Increasing demands for renewable energy encourage the development of inverters as a solution for converting energy from direct photovoltaic current (DC) output to alternative current (AC) at a maximum output power. Several nation standard systems are three-phase four-wired (TPFW), which means that the TPFW inverter must be used. The issue arises because the TPFW inverter is operated through an open-loop system, which has the problem of preventing the inverter from adjusting the voltage and current as needed. Hence, the open-loop system must be converted to a closed-loop system which is usually used only single control. The single strategy control is not effective because this strategy cannot regulate voltage and current at the same time. It only controls either voltage or current. The output voltage or current is changed when the load value is changed. Due to its weaknesses, the study proposes a new double-control strategy method that utilizes a PI strategy (P) controller as a voltage controller and a proportional strategy control as a current controller. This strategy is tested and measured by using simulation, showing a THD value of 1.07%. Accordance to IEEE standards, the THD value is within the recommended limit. Therefore, the output voltage and current produced have a good signal with a low ripple and stability without fluctuation.